Tibial tüberkül osteotomisinde üç farklı tespit yönteminin biyomekanik olarak karşılaştırılması / Biomechanically comparison of three fixation methods after tibial tubercle osteotomy - ERDEN, Tunay (Bezmialem Vakıf University, 2016)
Objective: In this study, it was aimed to biomechanically compare cannulated screw, cerclage and circular cable fixation methods after tibial tubercle osteotomy in calf tibia. Materials and Methods: For the purpose of study, 24 pieces of calf were used. The samples were divided into three groups of equal number of homogeneous bone mineral density (BMD). A standard plain tibial tubercle osteotomy was then performed on all specimens. Two 6,5 mm cannulated screws were used in group 1, three cables in group 2 and three cerclages in group 3. Samples were placed on the tester with an angle of 0 degrees between the patellar tendon and osteotomy line, and failure occurred with static loading after dynamic cyclic loading. Results: There was no failure occurred in the cyclic loading period in all three groups. According to the result of static loading, it was seen that fixation with cannulated screw provided more stable fixation at significant level. Conclusions: In order to avoid complications due to insufficient fixation after tibial tubercle osteotomy, we recommend to fix with tespitte cable (cable) if it is not suitable to use cannulated screw. Key words: tibial tubercle osteotomy, canulated screw, kablo, cerclage wire.

{{abstract}}
Thesis (Medical)--Bezmialem Vakıf University, Faculty of Medicine, Department of Orthopedics and Traumatology, Istanbul, 2016
Keywords: Ortopedi ve Travmatoloji = Orthopedics and Traumatology